2018
DOI: 10.1016/j.jbiomech.2018.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Local and global measurements show that damage initiation in articular cartilage is inhibited by the surface layer and has significant rate dependence

Abstract: Cracks in articular cartilage are a common sign of joint damage, but failure properties of cartilage are poorly understood, especially for damage initiation. Cartilage failure may be further complicated by rate-dependent and depth-dependent properties, including the compliant surface layer. Existing blunt impact methods do not resolve local cartilage inhomogeneities and traditional fracture mechanics tests induce crack blunting and may violate underlying assumptions of linear elasticity. To address this knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…30,31 Previous studies have shown the surface acts as the primary shear energy dissipating region with damage to this region exacerbating the effect of shear stress elsewhere in the tissue, which is consistent with the results of this study. [44][45][46] The protective nature of cartilage could be due to its inhomogeneous nature where the superficial layer is more compliant than the bulk, which results in the strain, and therefore the majority of cellular damage, being concentrated at the surface. 46,47 Next, the cellular damage caused by sliding motion is consistent with previous studies showing that the shear strain produced, at physiologic sliding speeds, similar levels of chondrocyte death at the superficial layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Previous studies have shown the surface acts as the primary shear energy dissipating region with damage to this region exacerbating the effect of shear stress elsewhere in the tissue, which is consistent with the results of this study. [44][45][46] The protective nature of cartilage could be due to its inhomogeneous nature where the superficial layer is more compliant than the bulk, which results in the strain, and therefore the majority of cellular damage, being concentrated at the surface. 46,47 Next, the cellular damage caused by sliding motion is consistent with previous studies showing that the shear strain produced, at physiologic sliding speeds, similar levels of chondrocyte death at the superficial layer.…”
Section: Discussionmentioning
confidence: 99%
“…30 Minor superficial cracking without fibrillation was observed at the cartilage surface, which may be responsible for the increased damage in cartilage that was impacted before sliding is due to the integrity of the superficial layer being compromised, making it resemble cartilage samples in previous studies where the surface is removed before impact. 31,45 This shows the need of an alternative shear energy dissipation mechanism once the surface becomes compromised. Lubrication of the cartilage sliding surfaces has been shown to assist in this function with alteration to the lubricant's lubricating properties being capable of mitigating or agitating cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Large crack lengths and severe damage to microstructural features were induced under relatively high-frequency compressive loading 30 , 31 . Recently, the authors and others found that impact loading, simulating the onset of post-traumatic OA, caused fissures and cracks 32 34 and that crack nucleation in cartilage was largely rate-dependent 35 , 36 . In particular, the authors observed that the solid matrix around the crack surfaces underwent larger relaxation and rearrangement at the slow loading rate compared to the fast loading rate 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The results are compared to the experimentally observed FCD loss of cartilage around cracks in vitro in the absence of exogenous inflammatory cytokine challenge. We hypothesize that, due to the non-uniform strain distributions found earlier around cartilage lesions 30 , 33 , 34 , the strain-based algorithm in the models causes a non-uniform FCD loss. On the other hand, because fluid pressure at the inner crack surface is negligible and uniform through the crack depth, the FCD loss is hypothesized to be more uniformly distributed around lesions in the fluid velocity-controlled degeneration algorithm.…”
Section: Introductionmentioning
confidence: 99%